Ensuring Suitability of Ground Support Equipment: The Role of AMC in Maintenance Supervision - Sari, Mustika; Virgie Priskila; Alit Sodikin (BRIN Publishing, 2025)
The decision of Apron Movement Control (AMC) in supervising the feasibility of Ground Support Equipment (GSE) is a crucial aspect of airport operations to ensure the safety and efficiency of flight services. This study aims to develop an effective and comprehensive decision-making model in assessing the feasibility of GSE using the Analytical Network Process (ANP) method. The research was conducted at Yogyakarta International Airport, Indonesia involving various criteria and subcriteria which include Engines, Safety Features, Vehicle Operation Licenses. The ANP method was chosen because of its ability to handle complex relationships and interrelationships between various assessment elements. The data was obtained through a questionnaire filled out by experts and related industry players, then analyzed to determine the weight and priority of each criterion. The results of the analysis show that Document Validity, Corrective Actions and Leaks have the greatest influence in the feasibility assessment of GSE. This study is expected to make a significant contribution to improving GSE safety standards and operational efficiency at airports, as well as a reference for AMC in conducting more structured and systematic supervision. The findings are also expected to encourage the application of the ANP method in various aspects of feasibility assessment and other managerial decisions in the aviation industry.